Speech perception under adverse conditions: insights from behavioral, computational, and neuroscience research - Guediche, Sara; Blumstein, Sheila; Fiez, Julie; Holt, Lori L. (Frontiers in Systems Neuroscience, 2014)
Adult speech perception reflects the long-term regularities of the native language, but it is also flexible such that it accommodates and adapts to adverse listening conditions and short-term deviations from native-language norms. The purpose of this review article is to examine how the broader neuroscience literature can inform and advance research efforts in understanding the neural basis of flexibility and adaptive plasticity in speech perception. In particular, we consider several domains of neuroscience research that offer insight into how perception can be adaptively tuned to short-term deviations while also maintaining without affecting the long-term learned regularities for mapping sensory input. We review several literatures to highlight the potential role of learning algorithms that rely on prediction error signals and discuss specific neural structures that are likely to contribute to such learning. Already, a few studies have alluded to a potential role of these mechanisms in adaptive plasticity in speech perception. Better understanding the application and limitations of these algorithms for the challenges of flexible speech perception under adverse conditions promises to inform theoretical models of speech.